2019
DOI: 10.4103/jpbs.jpbs_82_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of blood pressure control and associated factors among patients with hypertension in Iraq: a prospective cross-sectional study

Abstract: A bstract Background: Uncontrolled blood pressure (BP) is a major contributor to cardiovascular disease–related morbidity and mortality. However, evidence regarding the rate and factors associated with uncontrolled BP in Iraq is scarce. The objectives of this study were a) to assess the magnitude of and factors associated with patient BP control and b) to investigate the patient-level prescribing patterns of antihypertensive medications, in a large Iraqi hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…We found a significant association between total adherence scores and BP control (U = 1116, p = 0.001). This finding is consistent with the findings from several other studies [27,[32][33][34][35]. For example, an Ethiopian study conducted by Animut et al in 2018 reported that patients who were highly adherent to their antihypertensive medications were two times more likely to have controlled BP than those with low adherence [32].…”
Section: Adherencesupporting
confidence: 90%
See 2 more Smart Citations
“…We found a significant association between total adherence scores and BP control (U = 1116, p = 0.001). This finding is consistent with the findings from several other studies [27,[32][33][34][35]. For example, an Ethiopian study conducted by Animut et al in 2018 reported that patients who were highly adherent to their antihypertensive medications were two times more likely to have controlled BP than those with low adherence [32].…”
Section: Adherencesupporting
confidence: 90%
“…However, some studies have suggested that old age is considered as a barrier to optimal BP control and a strong predictor of uncontrolled HTN according to reported data from Singapore and Sweden, respectively [43,44]. In addition, the evidence from an Iraqi study did not support the significant impact of education and employment on the control of BP among hypertensive patients [34].…”
Section: Pandemic Impact and Socio-demographicsmentioning
confidence: 98%
See 1 more Smart Citation
“…Hypertension is a highly prevalent condition that significantly increases a patient’s risk of developing cardiovascular disease (CVD), the leading cause of death from non-communicable causes globally [ 3 ]. For the treatment of hypertension, renin–angiotensin–aldosterone system inhibitors (RAASis) are the most widely prescribed class of drugs, including angiotensin-converting enzyme inhibitors (ACEis) and angiotensin-receptor blockers (ARBs), the two most clinically relevant anti-hypertensive agents [ 7 12 ]. While RAASi are generally prescribed as a first-line therapy, poorly controlled hypertension is often managed with the addition of calcium channel blockers (CCBs) and diuretics [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…T2DM frequently coincides with hypertension and about 68.4% of T2DM patients have hypertension in the USA [6]. T2DM coupled with age and sex are the strongest predictors of uncontrolled blood pressure (BP) [7]. T2DM is usually associated with chronic inflammation due to metabolic syndrome-related immune system dysregulations [8,9].…”
Section: Introductionmentioning
confidence: 99%